Aplikasi Hidroksiapatit Sebagai Adsorben Kolesterol - Hidayat, Muhammad Ariful; Azis, Yelmida; Irianty, Rozanna Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite is a natural mineral form of calcium apatite and is a major inorganic component of human hard tissue, such as bones and teeth. Synthetic hydroxyapatite, is widely used as implant and filler material for bone and tooth decay, catalyst, carrier catalyst and adsorbent. Synthetic hydroxyapatite has a large and porous surface area, which makes it very advantageous to be used as an adsorbent. Hydroxyapatite has been widely used as an adsorbent for alkali metals and heavy metals. In this study synthetic hydroxyapatite is used as an adsorbent for cholesterol compounds in the solvent of hexane-ethyl acetate mixture. The study was carried out with variations of hydroxyapatite mass (0.5, 0.75, and 1.0 gram) and cholesterol concentrations (50, 75 and 100 ppm) at a stirring rate of 100 rpm at room temperature. Adsorbed cholesterol was then analyzed using a UV-Vis spectrophotometer. From UV-Vis spectrophotometer analysis,it was found that be known the efficiency of adsorption process reaches 48.9% and the adsorption capacity is up to 6.87 mg / gram.Keywords: adsorbent, cholesterol, hydroxyapatite